2010
DOI: 10.1016/j.heares.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative lead exposure and age-related hearing loss: The VA Normative Aging Study

Abstract: Although lead has been associated with hearing loss in occupational settings and in children, little epidemiologic research has been conducted on the impact of cumulative lead exposure on age-related hearing loss in the general population. We determined whether bone lead levels, a marker of cumulative lead exposure, are associated with decreased hearing ability in 448 men from the Normative Aging Study, seen between 1962 and 1996 (2,264 total observations). Air conduction hearing thresholds were measured at 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 45 publications
8
67
0
Order By: Relevance
“…Second, exposure to lead and cadmium has been related to a higher risk of several pathologic conditions that are also linked to frailty. Environmental exposure to lead in the elderly has been associated with cognitive decline (Bandeen-Roche et al 2009;Grashow et al 2013;Nordberg et al 2000;Power et al 2014;Shih et al 2006;van Wijngaarden et al 2011), impaired motor skills (Grashow et al 2013), increased blood pressure (Perlstein et al 2007), ischemic heart disease (Jain et al 2007), decreased renal function (Tsaih et al 2004), falls and fractures in women (Khalil et al 2008), hearing loss (Park et al 2010) and vision problems (Schaumberg et al 2004;Wu et al 2014). Cadmium, for which fewer studies have been conducted in the elderly, has also been associated with an increased risk of atherosclerotic plaques (Fagerberg et al 2012), peripheral artery disease (Tellez-Plaza et al 2013a), osteoporosis (Engstrom et al 2011;Gallagher et al 2008) and macular degeneration (Shiue 2013;Wu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Second, exposure to lead and cadmium has been related to a higher risk of several pathologic conditions that are also linked to frailty. Environmental exposure to lead in the elderly has been associated with cognitive decline (Bandeen-Roche et al 2009;Grashow et al 2013;Nordberg et al 2000;Power et al 2014;Shih et al 2006;van Wijngaarden et al 2011), impaired motor skills (Grashow et al 2013), increased blood pressure (Perlstein et al 2007), ischemic heart disease (Jain et al 2007), decreased renal function (Tsaih et al 2004), falls and fractures in women (Khalil et al 2008), hearing loss (Park et al 2010) and vision problems (Schaumberg et al 2004;Wu et al 2014). Cadmium, for which fewer studies have been conducted in the elderly, has also been associated with an increased risk of atherosclerotic plaques (Fagerberg et al 2012), peripheral artery disease (Tellez-Plaza et al 2013a), osteoporosis (Engstrom et al 2011;Gallagher et al 2008) and macular degeneration (Shiue 2013;Wu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Chuang et al [2007] calculated the PTA using the frequencies 0.5, 1, and 2 kHz in a group of industry workers and reported that the PTA of the right and left ears were increased by 6.14 and 7.99 dB, respectively, with a 10-fold increment of the blood lead level. In addition, a longitudinal study of 448 men found that an increase in tibia lead levels of 15 ÎŒg/g was associated with an OR of 1.19 (95% CI 0.92-1.53) and an increase in patella lead levels of 21 ÎŒg/g was associated with an OR of 1.48 (95% CI 1.14-1.91) for hearing loss measured in the speech frequency [Park et al, 2010]. In a recent study on the general Korean population, participants in the highest quintile of blood lead (2.920-26.507 ÎŒg/dL) had an OR of 1.52 (95% CI 1.11-2.10) for hearing loss in the frequencies 2, 3, and 4 kHz, compared to those in the lowest quintile (0.260-1.365 ÎŒg/dL), with a significant linear trend [Huh et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…The hearing ability of a person can be easily determined using the average of hearing threshold levels at specified frequencies; however, there is no international guideline from which to choose the appropriate frequencies. A few studies that reported the association between heavy metal exposure and hearing loss calculated the PTA variably in the frequency range of 0.5-8 kHz, and most of those studies commonly used the range 0.5-4 kHz (the socalled speech frequency) [Counter et al, 1997;Chuang et al, 2007;Hwang et al, 2009;Park et al, 2010;Shargorodsky et al, 2011;Choi et al, 2012;Saunders et al, 2013;Choi and Kim, 2014;Huh et al, 2016;Choi and Park, 2017]. However, the PTA that is determined using the speech frequency is likely to underestimate the degree of hearing loss, because lead and cadmium affect the highfrequency hearing ability rather than the low-frequency hearing ability.…”
Section: Introductionmentioning
confidence: 99%
“…These OELs are not consensus standards. TLVs are considered voluntary exposure guidelines for use by industrial hygienists and others trained in this discipline "to assist in the control of health hazards" [ACGIH Health Hazard Evaluation Report 2013-0130-3226 exposure can help prevent or delay development of age-related hearing loss [Park et al 2010].…”
Section: Appendix B: Figuresmentioning
confidence: 99%